Implikasi Putusan Mahkamah Konstitusi No. 135/PUU-XXII/2024 tentang Pemisahan Pemilu Nasional dan Lokal serta Dampaknya Terhadap Masa Jabatan Kepala Daerah dan DPRD - Moch Fiqri Zainurahman; Gunawan Gunawan; Khulaila Inda Fikriyah (JURNAL TERAPAN PEMERINTAHAN MINANGKABAU, 2025)
This study examines the implications of the Constitutional Court Decision Number 135/PUU-XXII/2024, which is legally final, binding, and applies erga omnes, thereby requiring a restructuring of Indonesia’s electoral system by separating national and local elections into two distinct stages with a minimum interval of two years and a maximum of two and a half years. This separation effectively ends the five-ballot simultaneous election model and significantly affects the synchronization of terms for the President and Vice President, DPR, DPD, regional heads, and local parliaments. The new framework introduces constitutional challenges, particularly regarding the potential extension of terms for regional heads and local legislators beyond the five-year period or filling vacancies through appointed officials lacking direct electoral legitimacy. This research employs a normative legal approach based on constitutional analysis, electoral and regional election laws, Constitutional Court Decision 135/PUU-XXII/2024 and related rulings, as well as scholarly literature on constitutional law and democratic theory. The findings indicate that the 2–2.5-year gap between national and local elections may generate disharmony between the electoral calendar, term-of-office regulations, and the principle of periodic elections. The study concludes that although separating elections may reduce the complexity of the simultaneous five-ballot model, the restructuring demands meticulous regulatory engineering and a carefully designed transitional framework to remain aligned with constitutional principles, democratic accountability, and the sovereignty of the people.